Post marketing studies for safety, tolerability, and effectiveness of Himalaya’s comprehensive range of baby care products - Bisht, Surender Singh; Poddar, Mohit; Narayan, Jaiprakash; Harakchand, Akash; Barman, Diganta; Mallad, Veerabhadra; Kumawat, Rajesh (International Journal of Contemporary Pediatrics, 2025)
Background: The baby care product market has seen a substantial growth in the recent years which has resulted in an increased concern about the safety and tolerability of these products for babies aged 0-36 months. Due to their delicate skin, the infants are highly sensitive to the potential undesirable effects of chemicals present in such products. This study is conducted with Himalaya’s range of baby care products. To assess safety, tolerability and effectiveness of natural baby care products for newborns, infants and toddlers. Methods: These post marketing observational studies (PMOS) were conducted among 9000 babies (approx. 500 babies were allocated to each of the 18 products), enrolled at 25 different medical centres across India. Safety, tolerability and efficacy of Himalaya’s range of baby products were assessed after 15 days of usage. Mildness and gentleness of the products on babies’ skin was assessed through dermatological assessment by a pediatrician on the scale of 0-4 (0=No change and 4=excellent). The safety was assessed by continuous monitoring of any signs or symptoms of local intolerance, undesirable effects, and adverse events. Subjective assessments from parents/ caretakers were also recorded to know the tolerability and overall suitability of the test products. Results: The study ensured the ability to evaluate both the improvement of symptoms from the initial baseline and the potential reappearance of symptoms throughout the research period. The products showed, statistically significant improvement (p value of<0.05) in the softness and smoothness of baby’s skin along with keeping the skin moisturized. No product related local intolerance, undesirable effect or adverse events were observed or reported during the study. Conclusions: Himalaya's range of baby care products are well-tolerated and found to be safe, effective, and suitable for regular use in babies aged 0 to 36 months.